Editorial: Diseases affecting reproduction and the neonatal period in ruminants, Volume II - Canton, German Jose; Louge Uriarte, Enrique Leopoldo; Moore, Prando Dadin (Frontiers Media, 2022)
The papers included in this Research Topic focus on common infectious and parasitic disease agents that cause ruminant abortion and perinatal (Dorsch et al., Giannitti et al., Gondim and McAllister, Gual et al.) and neonatal mortality (Caffarena et al.).